Penerapan Metode AHP dan SAW untuk Penentuan Kenaikan Jabatan Karyawan - Permatasari Diah; Sartika Dewi; Suryati Suryati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2018)
This study aims to determine the promotion of employees at the Dinas Kesehatan South Sumatera by using the AHP (Analytic Hierarchy Process) dan SAW (Simple Additive Wieght) methods. The AHP method is used to determine the weight of each criterion, while the SAW method is used to determine the rank of employee promotion. This promotion process is made using the Microsoft Visual Studio programming language. The test in this study carried out using blackbox testing methods and accuray testing. The black box test results show that the system can run well according to it’s function, and then the accuracy testing is tested by comparing the results of the calculation from Dinas Kesehatan office. From the ealculation result of the AHP method, SAW method, and AHP &SAW method can be concluded, AHP & SAW methods are better then AHP or SAW methods. The accuracy of the AHP and SAW method in case 1 is 100%, in case 2 is 100%, and in case 3 is 50%.